Efeitos da mudança sintática na realização do sujeito pronominal no português da comunidade quilombola Mussuca - Silva, Jacson Baldoino (2023)
Brazilian Brazilian Portuguese, with respect to European Portuguese, has strategies that privilege pronominal subject completion and few situations in which the null pronominal subject is preferred - which are already characterized as resistance contexts (DUARTE, 1993, 1995, 2018a, 2019a). Among the authors who investigate the processes of variation and change of the "avoid pronoun" principle, as part of the Null Subject Parameter, Duarte's (1995) doctoral thesis is considered a milestone for studies of this phenomenon in Brazilian Portuguese, an importance that unfolds in the author's other works (DUARTE, 1993, 2018a, 2018b, 2019a, 2020). Thus, based on a review of duartine studies (DUARTE, 1993, 1995, 2018a, 2019a), demonstrating the factors that contributed to the parametric remarking of the "avoid pronoun" principle in Brazilian Portuguese since the second half of the nineteenth century, as well as a review of the process of Irregular Linguistic Transmission (LUCCHESI; BAXTER, 2009), placing it as one of the elements that contributed to parametric change in this variety, this study seeks to answer the problem-question: is the process of Irregular Linguistic Transmission a socio-historical parameter that contributes to a greater variation of the linguistic feature of realization or deletion of the pronominal subject in Afro-Brazilian Portuguese of the Mussuca community (Laranjeiras/SE)? In view of this question, following a quantitative methodology (GUY; ZILLES, 2007) and the assumptions of parametric sociolinguistics (TARALLO, 1987; TARALLO; KATO, 1989; DUARTE, 2016, 2019), this paper seeks to investigate the realization or deletion of the pronominal subject in Afro- Brazilian Portuguese of the Mussuca community as a linguistic trait that makes it possible to understand the history of the contacts of Portuguese in Brazil with African languages and the learning process of this language - through Irregular Linguistic Transmission - of the children of enslaved Africans. Considering this goal, Afro-Brazilian Portuguese from Mussuca was described, trying to understand the Irregular Linguistic Transmission by controlling the age range of the 10 research participants, comparing the results with data from Duarte (1993, 1995, 2018a, 2019a) - mainly, Almeida (2005), Lucchesi (2009c). Following the trend of change in Brazilian Portuguese, the 1056 data in the corpus showed a clear preference for the phonetic realization of the pronominal subject. However, unlike the studies of these authors, the highest rate of null pronominal subject was in the second person (singular/plural). This percentage can be explained by the presence of a significant number of interrogative sentences of the yes/no type, and equivalent situations, as a context of resistance of the null pronominal subject (DUARTE, 1993, 2018a). The statistical program used to run the data, Goldvarb X (SANKOFF; TAGLIAMONTE; SMITH, 2005), selected as groups of factors relevant to the occurrence of the null subject: semantic subject characterization, sentence type, grammatical person, number-personal desinence, gender and education. However, as in Lucchesi (2009c), age group was not selected as significant, indicating that, at the current stage of change and due to linguistic leveling (LUCCHESI, 2017), the marks of linguistic contacts have been erased in Afro-Brazilian Portuguese, with linguistic factors being more significant than social ones in the process of finalizing parametric remeasurement - as pointed out by Duarte (2019a).